Structural characteristics and formation mechanisms of crack-free multilayer TaC/SiC coatings on carbon-carbon composites - 李国栋 熊翔 黄伯云 黄可龙 (Transactions of Nonferrous Metals Society of China, 2008)
In order to improve high temperature （over 2 273 K） ablation resistance, TaC and TaC/SiC composite coatings were deposited on carbon-carbon composites by CVD method utilizing reactive TaCl2-C3H6-H2-Ar and TaCl5-C3H6-CH3SiCl3-H2-Ar systems respectively. The structure and morphology of these coatings were analyzed by XRD and SEM. The results show that the double carbide coatings have good chemical compatibility during preparation. Two distinctive composition gradients are developed and used to produce multilayer TaC/SiC coatings with low internal stress, free crack and good resistant to thermal shock. A transition layer consisting of either C-TaC or C-SiC formed between the coating and the C/C matrix can reduce the residual stress effectively. The processing parameters were optimized and the possible growth mechanisms for these coatings were proposed. A designing methodology to prepare high performance multilayer TaC/SiC composite coatings was developed.